Research progress on the pharmacological effects of matrine - Sun, Yanan; Xu, Lu; Cai, Qihan; Wang, Mengmeng; Wang, Xinliang; Wang, Siming; Ni, Zhiyu (Frontiers in Neuroscience, 2022)
Matrine possesses anti-cancer properties, as well as the prevention and treatment of allergic asthma, and protection against cerebral ischemia-reperfusion injury. Its mechanism of action may be (1) regulation of cancer cell invasion, migration, proliferation, and cell cycle to inhibit tumor growth; (2) reduction of oxidized low-density lipoprotein and advanced glycation end products from the source by exerting anti-inflammatory and antioxidant effects; (3) protection of brain damage and cortical neurons by regulating apoptosis; (4) restoration of the intestinal barrier and regulation of the intestinal microbiota. This article aims to explore matrine’s therapeutic potential by summarizing comprehensive information on matrine's pharmacology, toxicity, and bioavailability.